Iaşi Art Residency International Artist Residency Program. American Artist-In-Residence John Dillard - Palamar Ioana (Sciendo, 2021)
Iași Art Residency is an artistic residency program that takes place in Iasi and involves the monthly invitation of an international visual artist, in order to materialize a specific art project related to the experience lived in the cultural space of Iasi. The program aims to connect the students of the Faculty of Visual Arts and Design within "George Enescu" National University of Arts in Iași with the invited artists, in order to exchange artistic experiences. This article will briefly present the activity of the American resident artist John Dillard whuch took place here, in Iasi, in January and February 2019.